1995 IEEE Ultrasonics Symposium. Proceedings. An International Symposium
DOI: 10.1109/ultsym.1995.495796
|View full text |Cite
|
Sign up to set email alerts
|

Pulse elongation and deconvolution filtering for medical ultrasonic imaging

Abstract: are associated with pulse compression methods Abstract --_ Range sidelobe artifacts which can be reduced with a new method composed of Pulse Elongation and Deconvolution (PED). Both approaches yield similar signal-to-noise ratio (SNR) improvements. The deconvolution is implemented as a stabilized inverse filter. The mean square error (MMSE) sense. An analytlcal excitation wave form is optimized in a minimum expression for the power spectrum of the optimal pulse is presented and several techniques t o numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…In this case deconvolving with the excitation waveform had several advantages; the excitation waveform was known because it was a part of the design and after the deconvolution with the excitation pulse, the resulted compressed echoes had similar waveform characteristics as those, which were obtained with a conventional system. The results presented in [9] demonstrated that the range resolution obtained during in vivo imaging of liver at 3 MHz was comparable to that of the conventional pulse-echo system. Similarly, in [10] the penetration depth (and hence S/N ratio) improvement in a real-time imaging system using pulse and the pseudo chirp sequence excitation was reported.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this case deconvolving with the excitation waveform had several advantages; the excitation waveform was known because it was a part of the design and after the deconvolution with the excitation pulse, the resulted compressed echoes had similar waveform characteristics as those, which were obtained with a conventional system. The results presented in [9] demonstrated that the range resolution obtained during in vivo imaging of liver at 3 MHz was comparable to that of the conventional pulse-echo system. Similarly, in [10] the penetration depth (and hence S/N ratio) improvement in a real-time imaging system using pulse and the pseudo chirp sequence excitation was reported.…”
Section: Introductionmentioning
confidence: 54%
“…The improvement of the SNR gain in medical ultrasonic imaging was clearly demonstrated by Haider et al [9]. The gain was achieved by the elongation of the excitation pulse and employment of the deconvolution filter, which was implemented as a modified Wiener filter with the deconvolution kernel being the excitation waveform.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse compression is a technique that is used in a wide range of applications, including the ultrasonic testing of concrete (Chang & Lee, 2004) and in medical ultrasonic imaging (Haider, Lewin, & Thomenius, 1998;O'Donnell, 1992;Misaridis et al, 2000). There are many types of waveform that could be used to achieve pulse compression (Behar & Adam, 2004).…”
Section: ¼J âB ð1þmentioning
confidence: 99%
“…However, the major problem associated with coded excitation is the range sidelobe artifacts [7][8][9][10]19]. In the Barker-13 coded excitation system, the peak sidelobe level (PSL) of matched filtered output is −22.3 dB below the mainlobe, which is not tolerated in medical ultrasound imaging.…”
Section: Introductionmentioning
confidence: 99%